Geopolymer grouting material as well as preparation method and application thereof
By using limestone stone powder, slag and fly ash and combining with alkali exciter to stimulate the reaction, a geopolymer grouting material with short solidification time and high compressive strength was prepared, which solved the insufficient material performance and environment in the prior art. The problem of pollution has achieved environmentally friendly and economical application of building materials.
Patent Information
- Application Number
- CN202411136560.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-20
AI Technical Summary
The settling time and compressive strength of the existing polygluing materials are poor, and there are problems of high energy consumption and high pollution during the production process.
Using geopolymer grouting material composed of limestone stone powder, slag, fly ash and alkali exciters, the potential activity of fly ash and slag is enhanced through alkali excitation, and combined with the physical filling and chemical reaction of limestone powder, it is prepared. Galpolymer grouting material with short solidification time and high compressive strength.
It significantly improves the compactness and compressive strength of grouting materials, reduces production energy consumption and costs, and solves the waste of waste stone powder during limestone processing, and has good environmental and economic benefits.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of grouting materials, and in particular to a geopolymer grouting material and a preparation method and application thereof. Background Art
[0002] Grouting is to inject slurry with bonding properties into the gaps or cracks in the rock and soil through equipment such as grouting pumps. The slurry can solidify and harden after injection to achieve the effect of filling and reinforcement. The selection of grouting materials is extremely important, affecting the solidification and hardening time and reinforcement effect. Traditional grouting materials are mainly cement-based materials. This type of material has the advantages of certain fluidity, strong adaptability, simple and convenient construction process, etc. For example, the Chinese patent document with publication number CN103880372B discloses a cement-based grouting material for reinforcement and repair, its preparation method and its application; it adopts a variety of admixture composite technology, has high compressibility, and has excellent anti-seepage and compressive properties. However, the shortcomings are also more significant. For example, the consumption of cement is large and the cost is high; secondly, cement itself has problems such as high energy consumption and high pollution in the production process, which does not meet the requirements of contemporary sustainable development.
[0003] Geopolymer is formed by geopolymerization of silicon- and aluminum-containing materials under alkaline medium conditions. It is a three-dimensional network structure formed by connecting silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons at vertex angles. In recent years, geopolymer has gradually attracted attention due to its rich raw materials and low energy consumption. It can be applied to the field of environmentally friendly green building materials. For example, Chinese patent document with publication number CN105541140B discloses a geopolymer grouting material and its preparation method and application. It uses zeolite powder, fly ash and clay as raw materials. Under the stimulation of alkaline solution, the silicon-aluminum oxide in the zeolite powder and fly ash can be dissolved to form a cementitious material similar to cement, and then the silicon-oxygen bond and the aluminum-oxygen bond are broken and reorganized under the action of alkaline activator, and finally hardened and consolidated, which can wrap and cement sand particles. The setting time is about 6 to 9 hours, and the 7-day compressive strength is less than 5MPa. It performs poorly in setting time and strength.
[0004] Therefore, it is necessary to develop a material with excellent performance and environmental friendliness. Summary of the invention
[0005] The main purpose of the present invention is to provide a geopolymer grouting material and a preparation method and application thereof, aiming to solve the technical problems of poor setting time and strength of existing geopolymer grouting materials.
[0006] In order to achieve the above object, the first aspect of the present invention provides a geopolymer grouting material, which is composed of the following components in parts by weight:
[0007] Dry powder, including 30 parts of limestone powder, 40-70 parts of slag, and 0-30 parts of fly ash;
[0008] 43-49 parts of alkali activator;
[0009] 0-2 parts of composite admixture solution;
[0010] The alkaline activator is a sodium silicate solution with a modulus of 1 to 1.5;
[0011] The composite admixture solution is prepared from a water reducing agent, a retarder and water;
[0012] The total amount of water in the alkaline activator and the composite admixture solution is 35 wt % to 39 wt % of the dry powder.
[0013] Further, it is composed of the following components in parts by weight:
[0014] Dry powder, including 30 parts of limestone powder, 60 parts of slag, and 10 parts of fly ash;
[0015] 43 parts of alkali activator;
[0016] 2 parts of composite admixture solution;
[0017] The alkaline activator is a sodium silicate solution with a modulus of 1.5;
[0018] The total amount of water in the alkaline activator and the composite admixture solution is 35 wt % of the dry powder.
[0019] Furthermore, the mass ratio of the water reducer, the retarder and water is 1:1:6.
[0020] Furthermore, the particle size of the limestone powder does not exceed 200 meshes.
[0021] Furthermore, the slag is S95 grade blast furnace granulated slag powder.
[0022] Furthermore, the fly ash is of grade I or II, and the total content of SiO2 and Al2O3 is not less than 80wt%.
[0023] Furthermore, the alkali activator is prepared by taking industrial water glass with a modulus of 2.3 to 3.4 as a raw material, adding sodium hydroxide and water.
[0024] Furthermore, the water reducer is a polycarboxylate-based high-efficiency water reducer; and the retarder is a zinc salt.
[0025] The second aspect of the present invention provides a method for preparing a geopolymer grouting material, which is used to prepare any of the above-mentioned geopolymer grouting materials, comprising the following steps:
[0026] (1) Weigh limestone powder, slag and fly ash by weight, and stir them evenly to obtain dry powder;
[0027] (2) diluting and mixing the water reducer, the retarder and water in a certain proportion to obtain a composite admixture solution;
[0028] (3) Adding the composite admixture solution and the alkali activator to the dry powder and stirring evenly to obtain the geopolymer grouting material.
[0029] The third aspect of the present invention provides an application of a geopolymer grouting material in repairing road damage.
[0030] Beneficial effects:
[0031] The geopolymer grouting material of the present invention enhances the potential activity of fly ash and slag through alkali activator, promotes geopolymer reaction, and uses limestone powder to physically fill pores and provide nucleation sites for chemical reactions to promote product generation, thereby effectively improving the compactness of the grouting material. Compared with traditional cement-based grouting materials, the geopolymer grouting material of the present invention has a shorter setting time, stronger compressive strength, lower energy consumption and cost in the production process, and can effectively solve the problem of waste caused by waste stone powder generated during limestone processing, turning waste into treasure, which is beneficial to environmental protection and can bring good economic and social benefits. DETAILED DESCRIPTION
[0032] The experimental methods in the following examples of the present invention, where no specific conditions are specified, are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The various commonly used chemical reagents used in the examples are all commercially available products.
[0033] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0034] The terms "including" and "having" and any variations thereof of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, device, product or equipment comprising a series of steps is not limited to the listed steps or modules, but may optionally include steps not listed, or may optionally include other steps inherent to these processes, methods, products or equipment.
[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0036] The present invention is further described in the following examples, but the examples are not intended to limit the scope of protection of the present invention.
[0037] An embodiment of the present invention provides a geopolymer grouting material, which is composed of the following components in parts by weight:
[0038] Dry powder, including 30 parts of limestone powder, 40-70 parts of slag, and 0-30 parts of fly ash;
[0039] 43-49 parts of alkali activator;
[0040] 0-2 parts of composite admixture solution;
[0041] The alkaline activator is a sodium silicate solution with a modulus of 1 to 1.5;
[0042] The composite admixture solution is prepared from a water reducing agent, a retarder and water;
[0043] The total amount of water in the alkaline activator and the composite admixture solution is 35 wt % to 39 wt % of the dry powder.
[0044] In the above embodiments, the main component of limestone powder is calcium carbonate, which has good stability, small particle size, can fill the microscopic pores of slag and fly ash, and is inexpensive; the non-metallic substances remaining after the metal is extracted from the ore during the metal smelting process of slag mainly include oxides such as silicon dioxide, iron oxide and calcium oxide or silicates such as calcium silicate and aluminum silicate; fly ash is mainly composed of unburned carbonaceous substances and minerals in coal; the present invention applies industrial by-products and industrial waste generated in the daily production process of building materials, steel, electric power and other industries to the field of grouting material preparation required for construction production.
[0045] The above-mentioned composite admixture is composed of two or more additives and water. The water reducer is used to improve the dispersibility, and the retarder further enhances the fluidity to prevent the setting time from being too fast to be inconvenient for subsequent operations. The total amount of water in the alkali activator and the composite admixture solution is limited, which ensures the fluidity without being too dilute to affect the strength after hardening.
[0046] The geopolymer grouting material of the present invention enhances the potential activity of fly ash and slag through alkali activator to generate geopolymer reaction, wherein limestone powder not only plays a role of physically filling pores, but also provides nucleation sites for chemical reactions to improve pore structure, has short solidification time and high compressive strength.
[0047] Compared with traditional cement-based grouting materials, the geopolymer grouting material of the present invention has lower energy consumption and cost in the production process, and can effectively solve the problem of waste stone powder generated during the processing of limestone, turning waste into treasure, which is beneficial to environmental protection and can bring good economic and social benefits.
[0048] In one embodiment, the geopolymer grouting material is composed of the following components in parts by weight:
[0049] Dry powder, including 30 parts of limestone powder, 60 parts of slag, and 10 parts of fly ash;
[0050] 43 parts of alkali activator;
[0051] 2 parts of composite admixture solution;
[0052] The alkaline activator is a sodium silicate solution with a modulus of 1.5;
[0053] The total amount of water in the alkaline activator and the composite admixture solution is 35 wt % of the dry powder.
[0054] Referring to Example 3, the amount of slag involved in the main reaction was increased, the amount of fly ash was reduced, the initial setting time and the final setting time were shortened, and the 28-day compressive strength reached 80 MPa.
[0055] In one embodiment, the mass ratio of the water reducer, the retarder and the water is 1:1:6.
[0056] In one embodiment, the particle size of the limestone powder does not exceed 200 meshes. The limestone powder has a smaller fineness and better dispersibility.
[0057] In one embodiment, the slag is S95 grade blast furnace granulated slag powder. Blast furnace granulated slag powder is a slag formed by quenching and granulating a molten material with silicate and aluminosilicate as main components when smelting pig iron in a blast furnace.
[0058] In one embodiment, the fly ash is of grade I or II, and the total content of SiO2 and Al2O3 is not less than 80wt%. Grade I or II fly ash has higher effective components such as SiO2 and Al2O3, and higher fineness requirements.
[0059] In one embodiment, the alkali activator is prepared by adding sodium hydroxide and water to industrial water glass with a modulus of 2.3 to 3.4 as a raw material. Industrial water glass with a modulus of 2.3 to 3.4 is relatively easy to obtain. In other embodiments, it can also be prepared from sodium silicate solutions with other moduli. The preparation process belongs to conventional technical means known to those skilled in the art.
[0060] In one embodiment, the water reducer is a polycarboxylate-based high-efficiency water reducer; the retarder is a zinc salt. The polycarboxylate-based high-efficiency water reducer is a new type of green and environmentally friendly water reducer, which has the advantages of high water reduction rate, small slump loss, high dispersibility, etc. Even when the content of the polycarboxylate water reducer is low, the geopolymer grouting material can have a higher fluidity; the retarder can keep the slurry plastic for a long time, thereby adjusting the setting time of the slurry. In addition to zinc salts, the retarder can also be barium salts, borax, etc.
[0061] Another embodiment of the present invention provides a method for preparing a geopolymer grouting material, which is used to prepare any of the above-mentioned geopolymer grouting materials, comprising the following steps:
[0062] (1) Weigh limestone powder, slag and fly ash by weight, and stir them evenly to obtain dry powder;
[0063] (2) diluting and mixing the water reducer, the retarder and water in a certain proportion to obtain a composite admixture solution;
[0064] (3) Adding the composite admixture solution and the alkali activator to the dry powder and stirring evenly to obtain the geopolymer grouting material.
[0065] Another embodiment of the present invention provides an application of a geopolymer grouting material in repairing road damage.
[0066] The specific embodiments are as follows:
[0067] Example 1
[0068] (1) Weigh 30 parts of limestone powder, 40 parts of slag and 30 parts of fly ash by weight, and stir them evenly to obtain a dry powder;
[0069] (2) diluting and mixing the polycarboxylate-based high-efficiency water reducer, the zinc sulfate retarder and water in a ratio of 1:1:6 to obtain a composite admixture solution;
[0070] (3) adding sodium hydroxide and water to water glass having a raw material modulus of 2.39 to prepare a sodium silicate solution having a modulus of 1.5 to obtain an alkali activator;
[0071] (4) adding 2 parts of the composite admixture solution and 43 parts of the alkali activator to the dry powder, and stirring evenly to obtain a geopolymer grouting material;
[0072] (5) Testing the setting time of the geopolymer grouting material obtained in step (4), injecting the geopolymer grouting material obtained in step (4) into a mold, curing it in a curing box, and measuring its compressive strength after 28 days.
[0073] Example 2
[0074] (1) Weigh 30 parts of limestone powder, 50 parts of slag and 20 parts of fly ash by weight, and stir them evenly to obtain a dry powder;
[0075] (2) diluting and mixing the polycarboxylate-based high-efficiency water reducer, the zinc sulfate retarder and water in a ratio of 1:1:6 to obtain a composite admixture solution;
[0076] (3) adding sodium hydroxide and water to water glass having a raw material modulus of 2.39 to prepare a sodium silicate solution having a modulus of 1.5 to obtain an alkali activator;
[0077] (4) adding 2 parts of the composite admixture solution and 43 parts of the alkali activator to the dry powder, and stirring evenly to obtain a geopolymer grouting material;
[0078] (5) Testing the setting time of the geopolymer grouting material obtained in step (4), injecting the geopolymer grouting material obtained in step (4) into a mold, curing it in a curing box, and measuring its compressive strength after 28 days.
[0079] The difference between Example 2 and Example 1 is only the addition amount of slag and fly ash.
[0080] Example 3
[0081] (1) Weigh 30 parts of limestone powder, 60 parts of slag and 10 parts of fly ash by weight, and stir them evenly to obtain a dry powder;
[0082] (2) diluting and mixing the polycarboxylate-based high-efficiency water reducer, the zinc sulfate retarder and water in a ratio of 1:1:6 to obtain a composite admixture solution;
[0083] (3) adding sodium hydroxide and water to water glass having a raw material modulus of 2.39 to prepare a sodium silicate solution having a modulus of 1.5 to obtain an alkali activator;
[0084] (4) adding 2 parts of the composite admixture solution and 43 parts of the alkali activator to the dry powder, and stirring evenly to obtain a geopolymer grouting material;
[0085] (5) Testing the setting time of the geopolymer grouting material obtained in step (4), injecting the geopolymer grouting material obtained in step (4) into a mold, curing it in a curing box, and measuring its compressive strength after 28 days.
[0086] The difference between Example 3 and Example 1 is only the addition amount of slag and fly ash.
[0087] Comparative Example 1
[0088] (1) Weigh 40 parts of slag and 60 parts of fly ash by weight, and stir them evenly to obtain dry powder;
[0089] (2) diluting and mixing the polycarboxylate-based high-efficiency water reducer, the zinc sulfate retarder and water in a ratio of 1:1:6 to obtain a composite admixture solution;
[0090] (3) adding sodium hydroxide and water to water glass having a raw material modulus of 2.39 to prepare a sodium silicate solution having a modulus of 1.5 to obtain an alkali activator;
[0091] (4) adding 2 parts of the composite admixture solution and 43 parts of the alkali activator to the dry powder and stirring evenly to obtain a slurry;
[0092] (5) Testing the setting time of the slurry obtained in step (4), injecting the slurry obtained in step (4) into a mold, curing it in a curing box, and measuring its compressive strength after 28 days.
[0093] The difference between Comparative Example 1 and Example 1 is that the limestone powder is replaced by fly ash.
[0094] Comparative Example 2
[0095] Ordinary Portland cement was used as raw material, and the water-cement ratio was 0.35. The setting time of the slurry obtained in comparative example 2 was tested, and the obtained slurry was injected into a mold, placed in a curing box for curing, and its compressive strength was measured after 28 days. Among them, the test method of setting time was carried out with reference to the national standard "Test method for cement standard consistency water consumption, setting time, and stability" GB / T1346, including initial setting time and final setting time; the compressive strength test method was carried out with reference to the national standard "Test method for cement mortar strength" GB / T17671.
[0096] The test results are shown in Table 1, which lists the setting time and compressive strength of the geopolymer grouting materials of Examples 1 to 3 and the slurries of Comparative Examples 1 to 2.
[0097] Table 1:
[0098]
[0099] The above results show that the initial setting time and final setting time of the geopolymer grouting materials containing limestone powder prepared in Examples 1 to 3 of the present invention are shorter than those of the comparative example, and the 28-day compressive strength of the geopolymer grouting materials containing limestone powder prepared in Examples 1 to 3 is stronger than that of the samples prepared in Comparative Examples 1 to 2, which indicates that compared with the traditional cement-based grouting material in Comparative Example 2, under the alkali excitation of water glass, the slag, fly ash and water glass undergo a geopolymer reaction, which effectively improves the strength of the grouting material, and increases the 28-day compressive strength by an average of 37%. The final setting time is shortened by 64%. Compared with Comparative Example 1, on the one hand, the added limestone powder in Example 1 can physically fill the pores and provide nucleation sites for chemical reactions to promote product formation, thereby effectively improving the compactness of the grouting material and thus achieving higher compressive strength. On the other hand, limestone powder is usually partially dissolved in water, and the introduction of calcium ions and the enhancement of the alkaline environment can accelerate the reaction rate of the geopolymer, causing the slurry to coagulate faster. This means that the geopolymer grouting material containing limestone powder of the present invention can better meet the rapid control of urban road and subway tunnel diseases and the application needs in related construction fields.
[0100] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A geopolymer grouting material, characterized in that: It is composed of the following components in parts by weight: Dry powder, including 30 parts of limestone powder, 40-70 parts of slag, and 0-30 parts of fly ash; 43-49 parts of alkali activator; 0-2 parts of composite admixture solution; The alkaline activator is a sodium silicate solution with a modulus of 1 to 1.5; The composite admixture solution is prepared from a water reducing agent, a retarder and water; The total amount of water in the alkaline activator and the composite admixture solution is 35 wt % to 39 wt % of the dry powder.
2. The geopolymer grouting material according to claim 1, characterized in that: It is composed of the following components in parts by weight: Dry powder, including 30 parts of limestone powder, 60 parts of slag, and 10 parts of fly ash; 43 parts of alkali activator; 2 parts of composite admixture solution; The alkaline activator is a sodium silicate solution with a modulus of 1.5; The total amount of water in the alkaline activator and the composite admixture solution is 35 wt % of the dry powder.
3. The geopolymer grouting material according to claim 1 or 2, characterized in that: The mass ratio of the water reducer, the retarder and water is 1:1:
6.
4. The geopolymer grouting material according to claim 1, characterized in that: The particle size of the limestone powder does not exceed 200 meshes.
5. The geopolymer grouting material according to claim 1, characterized in that: The slag is S95 grade blast furnace granulated slag powder.
6. The geopolymer grouting material according to claim 1, characterized in that: The fly ash is of grade I or II, and the total content of SiO2 and Al2O3 is not less than 80wt%.
7. The geopolymer grouting material according to claim 1, characterized in that: The alkali activator is prepared by taking industrial water glass with a modulus of 2.3 to 3.4 as a raw material and adding sodium hydroxide and water.
8. The geopolymer grouting material according to claim 1, characterized in that: The water reducer is a polycarboxylate-based high-efficiency water reducer; and the retarder is a zinc salt.
9. A method for preparing a geopolymer grouting material, used for preparing the geopolymer grouting material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weigh limestone powder, slag and fly ash by weight, and stir them evenly to obtain dry powder; (2) diluting and mixing the water reducer, the retarder and water in a certain proportion to obtain a composite admixture solution; (3) Adding the composite admixture solution and the alkali activator to the dry powder and stirring evenly to obtain the geopolymer grouting material.
10. Use of the geopolymer grouting material according to any one of claims 1 to 8 in repairing road damage.
